Development of a Moodle-based e-learning with the flipped classroom model to improve self-efficacy and Mathematics learning achievement - Amalia Husna; Amirunnizam Amirunnizam; Sofnidar Sofnidar; Khairul Anwar (JINoP (Jurnal Inovasi Pembelajaran), 2025)
Mathematics plays an important role in cognitive development. However, most students have low self-efficacy in mathematics. Low self-efficacy among students has an impact on their poor mathematics learning achievement. This study aims to develop Moodle-based e-learning using the flipped classroom model to enhance students’ self-efficacy and mathematics learning outcomes. This research employed a research and development (R&D) method using the ADDIE development model. The results of the study indicate that: (1) the development of Moodle-based e-learning with the flipped classroom model obtained a validity score percentage of 95% in terms of content and 95% in terms of media, both categorized as very valid; (2) it received practicality scores of 100% in the one-on-one trial and 90% in the small group trial, both categorized as very practical; and (3) it significantly improved students’ self-efficacy and mathematics learning outcomes, with N-gain values of 0.5 and 0.46 respectively, both categorized as moderate. The results of the independent samples t-test (two-tailed) showed a significance value of 0.000 < 0.05 with α = 0.05. Although this research was conducted during the COVID-19 pandemic when online learning was essential, the findings remain relevant and applicable in today's educational context. Even after the pandemic, as hybrid and digital learning become increasingly integrated with face-to-face learning, this model continues to offer significant benefits. It allows students to study materials independently outside the classroom and enhances meaningful interaction during in-person sessions. Therefore, the use of Moodle-based e-learning combined with the flipped classroom model can serve as a sustainable method to improve students' self-efficacy and mathematics learning outcomes in the long term.